Immune Evasion Strategies of Pre-Erythrocytic Malaria Parasites - Hong Zheng; Zhangping Tan; Wenyue Xu (Mediators of Inflammation)
Malaria is a mosquito-borne infectious disease of humans. It begins with a bite from an infected female Anopheles mosquito and leads to the development of the pre-erythrocytic and blood stages. Blood-stage infection is the exclusive cause of clinical symptoms of malaria. In contrast, the pre-erythrocytic stage is clinically asymptomatic and could be an excellent target for preventive therapies. Although the robust host immune responses limit the development of the liver stage, malaria parasites have also evolved strategies to suppress host defenses at the pre-erythrocytic stage. This paper reviews the immune evasion strategies of malaria parasites at the pre-erythrocytic stage, which could provide us with potential targets to design prophylactic strategies against malaria.